Faktor-Faktor yang Mempengaruhi Status Kemiskinan Pekerja di Provinsi Jambi - Taufiq, Taufiq; Junaidi, Junaidi; Denmar, Denmar (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The relationship between unemployment and poverty is not always in the same direction as we think so far. Status as an employee does not guarantee that someone will prosper, and status as unemployed does not always mean poor. Unemployment and poverty are not complementary variables and are not directly correlated. This study aims to provide an overview related to the profile or characteristics of working poor in Jambi Province. As well as to give an overview of what factors influence the poverty status of workers in Jambi Province. The type of data used in this research is secondary data in the form of raw data (micro data) for the August 2021 Sakernas sourced from the Central Bureau of Statistics (BPS). Meanwhile, to measure poverty in research workers will use the World Bank approach. Analysis was carried out using logistic regression analysis to obtain the determinants of workers' poverty status. The results of this study show a high level of significance and a clear trend effect on the probability of being working poor from the following variables: gender (female); marital status (not married); difference in educational level (elementary school and below); working hours (<35 hours a week); employment (services); employment status (self-employed/freelancer); do not have course/training experience; do not have a work contract; age group (61 years and over); and length of service in the job (risk decreases with length of employment).